Illustrating some principles of separation science through gravitational field-flow fractionation - Ronald Beckett (2018)
The theory and laboratory exercises being described is given to illustrate some general concepts of physical chemistry and separation science through gravitational field-flow fractionation (FFF). In addition, the FFF technique is being introduced to the undergraduate curriculum. The materials that will be used for the laboratory exercises are outlined that can be set as a standard practical exercise. This FFF theory can be combined in lectures while it gives experiments that can be included in laboratory classes. This gravitational FFF is inexpensive and easy to construct.